Prevalence of Delta-Like Protein 3 in a Consecutive Series of Surgically Resected Lung Neuroendocrine Neoplasms - Alì, Greta; Di Stefano, Iosè; Poma, Anello Marcello; Ricci, Stefano; Proietti, Agnese; Davini, Federico; Lucchi, Marco; Melfi, Franca; Fontanini, Gabriella (Frontiers in Oncology, 2021)
Delta-like protein 3 (DLL3) is a protein of the Notch pathway, and it is a potential therapeutic target for high-grade lung neuroendocrine tumours (NETs), i.e. small cell lung cancer (SCLC) and large cell neuroendocrine carcinoma (LCNEC). However, DLL3 prevalence in lung NETs and its association with clinico-pathological characteristics and prognosis remained unclear. We analyzed the immunohistochemical expression of DLL3 and its prognostic role in a consecutive series of 155 surgically resected lung neuroendocrine tumours, including typical carcinoid (TC), atypical carcinoid (AC), LCNEC, and SCLC patients. The DLL3 expression was categorized as high (50% positive tumour cells) or low (<50%). In addition, tumours were categorized by H-score (i.e. percentage of positive cells by staining intensity, ≥150 vs <150). DLL3 staining was positive in 99/155 (64%) samples and high DLL3 expression was frequently observed in high-grade tumours. In detail, 46.9% and 75% of SCLC and 48.8% and 53.7% of LCNEC specimens showed a high DLL3 expression by using H-score and percentage of positive tumour cells, respectively. Regarding low-grade NETs, only 4.9% and 12.2% TCs and 19.5% and 24.4% ACs had high DLL3 expression considering H-score and percentage of positive tumour cells, respectively. High DLL3 expression was associated with advanced AJCC stage, peripheral location and Chromogranin A expression in high-grade tumours (p < 0.05). In low-grade NETs, high DLL3 expression was associated with female sex, peripheral location, a higher number of mitoses, higher ki-67 index, presence of necrosis and pleural infiltration (p < 0.05). No association was observed between high DLL3 expression and overall survival (OS) and disease-free survival (DFS) in high-grade NETs, whereas high DLL3 expression was associated with lower DFS in atypical carcinoids (p=0.01). In conclusion, our study demonstrated a high prevalence of DLL3 expression in high-grade lung NET patients and its association with aggressive clinico-pathological features. These findings confirm that DLL3 could represent a useful biomarker for target therapy in high-grade tumours. Our results also suggest that the DLL3 expression could identify a subset of atypical carcinoid tumours with more aggressive behaviour, thus providing the basis for new therapeutic options in this group of patients.